Penatalaksanaan Benda Asing Intraokular: Tinjauan Pustaka - Iskandar, Ferdy; Angelia, Maria (PT Kalbe Farma Tbk., 2024)
Intraocular foreign body (IOFB) is an ophthalmologic emergency, demanding immediate diagnosis and treatment to prevent blindness and eye loss. These foreign bodies may penetrate via cornea (62%), sclera (25%), or limbus (10%), most IOFB resides in the posterior segment of the eye (58%-88%). Early treatment plays a pivotal role in providing a favorable patient prognosis.